Sistema piloto de adsorção de íons de metais em coluna (leito fixo) utilizando como adsorvente o pó da casca de coco verde - Raulino, Giselle Santiago Cabral (2011)
The agro-industrial residues have been used in research as adsorbents of toxic metals from aqueous effluents due to its low cost, high availability and efficiency for this purpose. In this study, residues from coconut shell industry was used, the coconut husk, from EMBRAPA, as adsorbent material of copper, nickel and zinc from aqueous solutions on a pilot scale. First, was made the determination of particle size material, showing that about 85% was found in the range of 10 to 60mesh. Then, the effects of physical and chemical treatment on the metals adsorption. The two treatments selected was NaOH 0.1 mol.L-1 and water, because there was an increase in the adsorption capacity. Then, was proceeded the column tests. In the optimization of operating parameters, the flow of 200mL.min-1 and bed height 100 cm, were chosen because of convenience, shorter execution time and ease of operation, and high adsorption capacities. The resulting TDH of parameters was 15min. After the optimization of operating parameters, we investigated the influence of treatment outside and inside the column. It was observed that, in general, the adsorption capacity increased when the material is subjected to treatment with 0.1 M NaOH inside the column in relation to water treatments in and ouside the column and NaOH outside the column. The adsorption capacity of multielement system for the treatment with NaOH in the column were: 32.2 mg.g-1 for copper, 10.86 mg.g-1 for nickel and 7.97 mg.g-1 for zinc. It was also seen that the solution resulting from this treatment requires correction of pH and COD treatment for disposal. The adsorption capacity increased for monoelementar system in comparison with a multielement system, resulting in: 39.37 mg.g-1 for copper, 21.9 mg.g-1 for nickel and 20.6 mg. g-1 for zinc. The desorption using HNO3 0.5 mol.L-1- as eluent needed about 20 L to remove the metals adsorbed on the shell powder coconut treated.